A bacterial cellulose-based biomaterial and a method for preparing the same

CN121059868BActive Publication Date: 2026-10-09NANJING TIANLU NANOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511345733.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2026-10-09
Estimated Expiration
2045-09-19

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种细菌纤维素基生物材料及其制备方法,其解决了现有应用于伤口敷料的细菌纤维素基生物材料所存在的抗菌效果不长久的问题

Benefits of technology

[0024] (1) The biomaterial of the present invention has a dual-functional surface structure. One side is a dense and porous mineral layer. When it comes into contact with the outside world, the nano zinc phosphate barrier formed can act as a physical and chemical barrier to effectively block bacteria. At the same time, the microporous structure allows for free gas exchange, effectively ensuring antibacterial and breathable properties. The other side maintains the inherent high porosity three-dimensional network structure of BC. When it comes into contact with the wound, its high water retention properties can be used to absorb exudate and promote wound repair. In addition, the present invention uses the strong adhesion of the polydopamine layer to firmly anchor the broad-spectrum antimicrobial peptides inside the BC fiber network. In a moist environment, the polydopamine will slowly release the antimicrobial peptides, achieving a long-lasting and controllable antibacterial effect on the wound surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121059868B_ABST
    Figure CN121059868B_ABST
Patent Text Reader

Abstract

The application discloses a kind of bacterial cellulose-based biomaterial and its preparation method in the field of biomedical materials, method steps include: taking Komagataella pastoris, obtains BC hydrogel membrane by fermentation, purification, drying;Take BC hydrogel membrane and form dense porous mineral layer by adding zinc sulfate solution and sodium phosphate solution in turn;BC hydrogel membrane is immersed into dopamine hydrochloride solution again, and form polydopamine layer;BC hydrogel membrane is immersed into antibacterial peptide solution, and antibacterial peptide is anchored to BC hydrogel membrane;BC hydrogel membrane is post-treated, and it is obtained.This biomaterial has bifunctional surface structure, one side is dense porous mineral layer, which can efficiently physically block bacteria, while microporous structure allows gas to exchange freely;The other side contacts wound, and high water retention characteristics can be used to absorb exudate, promote wound repair;And polydopamine layer can achieve long-acting controllable antibacterial effect in wound surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, specifically to a bacterial cellulose-based biomaterial and its preparation method. Background Technology

[0002] Bacterial cellulose (BC)-based biomaterials are high-performance biopolymers synthesized by microorganisms. With their unique physicochemical properties and excellent biocompatibility, they demonstrate application potential in multiple fields. Particularly in medical materials, they can be used as wound dressings, artificial skin, dura mater repair, tympanic membrane reconstruction materials, and tissue engineering scaffolds. The preparation of bacterial cellulose-based biomaterials is a multi-step process, mainly including the biosynthesis of bacterial cellulose and subsequent functionalization. The biosynthesis of bacterial cellulose is primarily achieved through microbial fermentation, with commonly used strains including *Komagataeibacter xylinus* and *Gluconacetobacter xylinus*. Functionalization modification is diverse and can be freely selected according to specific functional requirements, including inorganic composites, organic composites, loading with bioactive substances, and chemical modification.

[0003] Bacterial cellulose-based biomaterials used in wound dressings can provide oxygen and moisture permeability, protect the wound surface, prevent infection, and promote healing. This also requires the materials to have good breathability and antibacterial properties. Most existing bacterial cellulose medical dressings directly use a mesh-like porous membrane structure to increase breathability, while simultaneously loading antibacterial factors (such as Ag and ZnO) to impart antibacterial properties. However, this mesh-like porous membrane allows for continuous bacterial invasion, and the antibacterial effect of the loaded antibacterial factors gradually diminishes, leading to a significant decrease in the dressing's antibacterial performance after a period of use, which also affects wound healing. Summary of the Invention

[0004] The purpose of this invention is to provide a bacterial cellulose-based biomaterial and its preparation method, which solves the problem of short-lasting antibacterial effect of existing bacterial cellulose-based biomaterials used in wound dressings.

[0005] The present invention achieves the above objectives through the following technical solutions:

[0006] A method for preparing bacterial cellulose-based biomaterials, comprising the following steps:

[0007] S1. Take *Odontobacterium micranthum*, and obtain BC hydrogel membrane through fermentation, purification, and drying;

[0008] S2. Place the BC hydrogel membrane flat on a polytetrafluoroethylene plate, and uniformly drop zinc sulfate solution onto the surface of the BC hydrogel membrane. After dropping, let it stand for 30-40 minutes to allow the Zn solution to settle. 2+ The solution penetrates into the surface fiber network of the BC hydrogel membrane, and then the residual zinc sulfate solution is removed. Next, sodium phosphate solution is added dropwise to the surface of the BC hydrogel membrane in the same manner, allowing PO4 to penetrate. 3- It penetrates into the surface fiber network of the BC hydrogel membrane and interacts with Zn. 2+ The reaction occurs in the fiber network, generating zinc phosphate crystals in situ and forming a dense, porous mineral layer. Finally, the BC hydrogel membrane is rinsed with deionized water.

[0009] S3. Then turn the BC hydrogel membrane over and immerse it in a dopamine hydrochloride solution. Shake it at room temperature in the dark for 6-12 hours to allow dopamine to self-polymerize under the action of dissolved oxygen and form a polydopamine layer on the surface of the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with deionized water.

[0010] S4. After sealing the mineral layer surface of the BC hydrogel membrane, immerse it in the antimicrobial peptide solution and shake it for 12-24 hours. This allows the catechol / quinone groups on the surface of the dopamine salt to undergo a Michael addition reaction with the amino groups of the antimicrobial peptide molecules and form a covalent bond, thus anchoring the antimicrobial peptide to the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with PBS buffer.

[0011] S5. The BC hydrogel membrane is sequentially rinsed with deionized water, freeze-dried, sterilized, and encapsulated to obtain the bacterial cellulose-based biomaterial.

[0012] The further improvement lies in the fact that the specific operation of step S1 is as follows:

[0013] Frozen *Coprinus coprinus* was inoculated into HS plates and cultured at 28-30℃ for 36-48 h to activate it. Then, a single colony of *Coprinus coprinus* from the HS plate was inoculated into HS medium and cultured at 28-30℃ with stirring at 120-180 rpm for 18-36 h to obtain a seed solution. The seed solution was then added to HS medium at an inoculation rate of 4-5% and statically cultured at 28-30℃ for 72-120 h to ferment and obtain BC hydrogel. The BC hydrogel was then immersed in a 1-2% NaOH solution for 60-80 min, removed, and washed with deionized water until neutral. Finally, the BC hydrogel was air-dried at room temperature to obtain the BC hydrogel membrane.

[0014] A further improvement is that the *Komagataeibacter* species is selected from one of *Komagataeibacter xylinus*, *Komagataeibacter accharivorans*, or *Komagataeibacter hansenii*.

[0015] A further improvement is that the HS culture medium consists of: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, and 1.5 g / L citric acid monohydrate.

[0016] A further improvement is that the HS culture medium consists of: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, 1.5 g / L citric acid monohydrate, and 1 g / L hydrophobic ficus seed gum powder.

[0017] The preparation steps of the hydrophobic fig seed gum powder are as follows: After washing and removing impurities from fig seeds, soak them in warm water at 40-50℃ for 2-4 hours, then grind them using a tissue homogenizer for 3-5 minutes. Filter the pulp after grinding to remove the fig seed residue, obtaining a gum solution. Add 1.5-2.5 times the volume of anhydrous ethanol to the gum solution, allow it to settle, collect the precipitate, and repeat the steps of water dissolution and ethanol precipitation to finally obtain a pure filter cake. This cake is then crushed, dried, ground, and sieved to obtain fig seed gum powder. The fig seed gum powder is then prepared at a ratio of 1g:30... -40 mL of the solution was dissolved in deionized water at 35±2℃, and the pH was adjusted to 8-9 with NaOH. Then, 2-4% of the weight of the fig seed gum powder was added dropwise while stirring, and the reaction was carried out for 3-4 hours. After the reaction was completed, the pH of the reaction solution was adjusted to neutral with HCl. Then, 2-3 times the volume of anhydrous ethanol was added to the reaction solution, and the mixture was allowed to stand to precipitate. The precipitate was collected and the steps of water dissolution and ethanol precipitation were repeated to finally obtain a pure filter cake. The filter cake was then crushed, dried, ground, and sieved to obtain hydrophobic fig seed gum powder.

[0018] A further improvement is that, in step S2, the concentrations of zinc sulfate and sodium phosphate are 0.08-0.12 M, and the dropping volume is 0.12-0.15 mL / cm³. 2 .

[0019] A further improvement is that, in step S3, the dopamine hydrochloride solution is prepared using a Tris-HCl buffer solution with a pH of 8-9 and a concentration of 1.5-2.2 mg / mL.

[0020] A further improvement is that, in step S4, the antimicrobial peptide solution is selected from Cecropin B or human defensin HD-5, which are dissolved in PBS buffer and have a concentration of 0.5-1.0 mg / mL.

[0021] A further improvement is that, in step S4, the specific operation of sealing the mineral layer surface of the BC hydrogel film is to attach the mineral layer surface of the BC hydrogel film to a polytetrafluoroethylene sheet and seal the edges of the BC hydrogel film with silicone grease.

[0022] The present invention also provides a bacterial cellulose-based biomaterial, which is prepared by the aforementioned preparation method.

[0023] The beneficial effects of this invention are as follows:

[0024] (1) The biomaterial of the present invention has a dual-functional surface structure. One side is a dense and porous mineral layer. When it comes into contact with the outside world, the nano zinc phosphate barrier formed can act as a physical and chemical barrier to effectively block bacteria. At the same time, the microporous structure allows for free gas exchange, effectively ensuring antibacterial and breathable properties. The other side maintains the inherent high porosity three-dimensional network structure of BC. When it comes into contact with the wound, its high water retention properties can be used to absorb exudate and promote wound repair. In addition, the present invention uses the strong adhesion of the polydopamine layer to firmly anchor the broad-spectrum antimicrobial peptides inside the BC fiber network. In a moist environment, the polydopamine will slowly release the antimicrobial peptides, achieving a long-lasting and controllable antibacterial effect on the wound surface.

[0025] (2) The biomaterial of the present invention also has multiple antibacterial synergies (physical mineral layer barrier, micro-soluble Zn) 2+ It has advantages such as antimicrobial peptides, promoting healing, and good biocompatibility.

[0026] (3) In a preferred embodiment of the present invention, hydrophobic ficus seed gum powder is added to the bacterial cellulose culture medium. It is incorporated into the BC hydrogel membrane through in-situ fermentation, which can significantly improve the water retention and flexibility of the membrane. After being modified by hydrophobic octenyl succinic anhydride, it can be adsorbed on the surface of the hydrophobic crystalline region of BC fiber, thereby avoiding the impact on the porous structure of BC fiber. Attached Figure Description

[0027] Figure 1 SEM images of the microstructures of various bacterial cellulose-based biomaterial samples;

[0028] Figure 2 A statistical chart showing the swelling ratio of various bacterial cellulose-based biomaterial samples;

[0029] Figure 3 H&E staining images of rat wound tissues treated with various bacterial cellulose-based biomaterials. Detailed Implementation

[0030] The present application will now be described in further detail with reference to the accompanying drawings. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.

[0031] I. Main Materials

[0032] Oligococcus foetida: Self-preserved by the laboratory research and development team;

[0033] Zinc sulfate: purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;

[0034] Sodium phosphate: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0035] Dopamine hydrochloride: purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;

[0036] Antimicrobial peptides: purchased from Hebei Clavel Biotechnology Co., Ltd.

[0037] Fig seeds: purchased from Xianjun Department Store, Banan District, Chongqing;

[0038] Octenyl succinic anhydride: purchased from Shandong Xinheng Chemical Co., Ltd.

[0039] II. Conducting the Experiment

[0040] Example 1

[0041] A method for preparing bacterial cellulose-based biomaterials, comprising the following steps:

[0042] S1. Prepare HS medium (components: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, 1.5 g / L citric acid monohydrate). Inoculate frozen Komagataeibacter xylinus into HS plates and incubate at 28°C for 48 h to activate it. Then, take a single colony of Komagataeibacter xylinus from the HS plate and inoculate it into HS medium. Incubate at 28°C with stirring at 120 rpm for 36 h to obtain the seed solution. Add the seed solution to HS medium at an inoculation rate of 4% and incubate statically at 28°C for 120 h to obtain BC hydrogel. Then, immerse the BC hydrogel in a 1% NaOH solution for 80 min. After removing it, wash it with deionized water until neutral. Finally, air dry the BC hydrogel at room temperature to obtain the BC hydrogel membrane.

[0043] S2. Place the BC hydrogel membrane flat on a polytetrafluoroethylene plate, and uniformly drop zinc sulfate solution onto the surface of the BC hydrogel membrane. After dropping, let it stand for 30 minutes to allow the Zn solution to settle. 2+ The solution penetrates into the surface fiber network of the BC hydrogel membrane, and then the residual zinc sulfate solution is removed. Next, sodium phosphate solution is added dropwise to the surface of the BC hydrogel membrane in the same manner, allowing PO4 to penetrate. 3- It penetrates into the surface fiber network of the BC hydrogel membrane and interacts with Zn. 2+The reaction occurs within the fiber network, generating zinc phosphate crystals in situ and forming a dense, porous mineral layer. Finally, the BC hydrogel membrane is rinsed with deionized water. The concentrations of zinc sulfate and sodium phosphate are 0.08 M, and the addition rate is 0.12 mL / cm³. 2 .

[0044] S3. Next, turn the BC hydrogel membrane over and immerse it in a dopamine hydrochloride solution. Shake it at room temperature in the dark for 6 hours to allow dopamine to self-polymerize under the action of dissolved oxygen and form a polydopamine layer on the surface of the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with deionized water. The dopamine hydrochloride solution was prepared using Tris-HCl buffer solution with a pH of 8 and a concentration of 1.5 mg / mL.

[0045] S4. After sealing the surface of the mineral layer of the BC hydrogel membrane (the surface of the mineral layer is attached to a polytetrafluoroethylene sheet, and the edges of the BC hydrogel membrane are sealed with silicone grease), immerse it in the antimicrobial peptide solution and shake for 12 hours. This allows the catechol / quinone groups on the surface of the dopamine salt to undergo a Michael addition reaction with the amino groups of the antimicrobial peptide molecules and form covalent bonds, anchoring the antimicrobial peptide to the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with PBS buffer to remove the sealing sheet. The antimicrobial peptide solution used is human defensin HD-5, which is dissolved in PBS buffer and has a concentration of 0.5 mg / mL.

[0046] S5. The BC hydrogel membrane is sequentially rinsed with deionized water, freeze-dried, sterilized, and encapsulated to obtain the bacterial cellulose-based biomaterial.

[0047] Example 2

[0048] A method for preparing bacterial cellulose-based biomaterials, comprising the following steps:

[0049] S1. Prepare HS medium (components: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, 1.5 g / L citric acid monohydrate). Inoculate frozen Komagataeibacter accharivorans into HS plates and incubate at 30°C for 36 h to activate it. Then, take a single colony of Komagataeibacter accharivorans from the HS plate and inoculate it into HS medium. Incubate at 30°C with stirring at 180 rpm for 18 h to obtain the seed solution. Add the seed solution to HS medium at an inoculation rate of 5% and incubate statically at 30°C for 72 h to obtain BC hydrogel. Then, immerse the BC hydrogel in a 2% NaOH solution for 60 min. After removing it, wash it with deionized water until neutral. Finally, air dry the BC hydrogel at room temperature to obtain the BC hydrogel membrane.

[0050] S2. Place the BC hydrogel membrane flat on a polytetrafluoroethylene plate, and uniformly drop zinc sulfate solution onto the surface of the BC hydrogel membrane. After dropping, let it stand for 40 minutes to allow the Zn solution to settle. 2+ The solution penetrates into the surface fiber network of the BC hydrogel membrane, and then the residual zinc sulfate solution is removed. Next, sodium phosphate solution is added dropwise to the surface of the BC hydrogel membrane in the same manner, allowing PO4 to penetrate. 3- It penetrates into the surface fiber network of the BC hydrogel membrane and interacts with Zn. 2+ The reaction occurs within the fiber network, generating zinc phosphate crystals in situ and forming a dense, porous mineral layer. Finally, the BC hydrogel membrane is rinsed with deionized water. The concentrations of zinc sulfate and sodium phosphate are 0.12 M, and the addition rate is 0.15 mL / cm³. 2 .

[0051] S3. Next, flip the BC hydrogel membrane over and immerse it in a dopamine hydrochloride solution. Shake it at room temperature in the dark for 12 hours to allow dopamine to self-polymerize under the action of dissolved oxygen and form a polydopamine layer on the surface of the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with deionized water. The dopamine hydrochloride solution was prepared using Tris-HCl buffer solution with a pH of 9 and a concentration of 2.2 mg / mL.

[0052] S4. After sealing the surface of the mineral layer of the BC hydrogel membrane (the surface of the mineral layer is attached to a polytetrafluoroethylene sheet, and the edges of the BC hydrogel membrane are sealed with silicone grease), immerse it in the antimicrobial peptide solution and shake for 24 hours. This allows the catechol / quinone groups on the surface of the dopamine salt to undergo a Michael addition reaction with the amino groups of the antimicrobial peptide molecules and form covalent bonds, anchoring the antimicrobial peptide to the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with PBS buffer to remove the sealing sheet. The antimicrobial peptide solution used is Cecropin B, which is dissolved in PBS buffer and has a concentration of 1.0 mg / mL.

[0053] S5. The BC hydrogel membrane is sequentially rinsed with deionized water, freeze-dried, sterilized, and encapsulated to obtain the bacterial cellulose-based biomaterial.

[0054] Example 3

[0055] A method for preparing bacterial cellulose-based biomaterials, comprising the following steps:

[0056] S1. Prepare HS medium (components: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, 1.5 g / L citric acid monohydrate, 1 g / L hydrophobic ficus seed gum powder). Inoculate frozen Komagataeibacter accharivorans into HS plates and incubate at 30℃ for 36 h to activate it. Then, take a single colony of Komagataeibacter accharivorans from the HS plate and inoculate it into HS medium. Incubate at 30℃ and 180 rpm for 18 h to obtain the seed solution. Add the seed solution to HS medium at an inoculation rate of 5% and incubate statically at 30℃ for 72 h to obtain BC hydrogel. Then, immerse the BC hydrogel in a 2% NaOH solution for 60 min. After taking it out, wash it with deionized water until neutral. Finally, air dry the BC hydrogel at room temperature to obtain the BC hydrogel membrane.

[0057] The preparation steps of the hydrophobic fig seed gum powder are as follows: Fig seeds are washed and cleaned, then soaked in 45℃ warm water for 3 hours. The seeds are then crushed using a tissue homogenizer for 4 minutes. The crushed slurry is filtered to remove the fig seed residue, yielding a gum solution. Two volumes of anhydrous ethanol are added to the gum solution, and the mixture is allowed to settle. The precipitate is collected, and the steps of water dissolution and ethanol precipitation are repeated until a pure filter cake is obtained. This pure filter cake is then crushed, dried, ground, and sieved to obtain the fig seed gum powder. The fig seed gum powder is then prepared at a ratio of 1g:35mL. The solution was dissolved in deionized water at 35°C, and the pH was adjusted to 8.5 with NaOH. Then, octenyl succinic anhydride (3% of the mass of the fig seed gum powder) was added dropwise while stirring, and the reaction was carried out for 3.5 hours. After the reaction was completed, the pH of the reaction solution was adjusted to neutral with HCl. Then, 3 times the volume of anhydrous ethanol was added to the reaction solution, and the mixture was allowed to stand to precipitate. The precipitate was collected and the steps of water dissolution and ethanol precipitation were repeated to finally obtain a pure filter cake. The filter cake was then crushed, dried, ground, and sieved to obtain hydrophobic fig seed gum powder.

[0058] S2. Place the BC hydrogel membrane flat on a polytetrafluoroethylene plate, and uniformly drop zinc sulfate solution onto the surface of the BC hydrogel membrane. After dropping, let it stand for 40 minutes to allow the Zn solution to settle. 2+ The solution penetrates into the surface fiber network of the BC hydrogel membrane, and then the residual zinc sulfate solution is removed. Next, sodium phosphate solution is added dropwise to the surface of the BC hydrogel membrane in the same manner, allowing PO4 to penetrate. 3- It penetrates into the surface fiber network of the BC hydrogel membrane and interacts with Zn. 2+ The reaction occurs within the fiber network, generating zinc phosphate crystals in situ and forming a dense, porous mineral layer. Finally, the BC hydrogel membrane is rinsed with deionized water. The concentrations of zinc sulfate and sodium phosphate are 0.12 M, and the addition rate is 0.15 mL / cm³. 2 .

[0059] S3. Next, flip the BC hydrogel membrane over and immerse it in a dopamine hydrochloride solution. Shake it at room temperature in the dark for 12 hours to allow dopamine to self-polymerize under the action of dissolved oxygen and form a polydopamine layer on the surface of the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with deionized water. The dopamine hydrochloride solution was prepared using Tris-HCl buffer solution with a pH of 9 and a concentration of 2.2 mg / mL.

[0060] S4. After sealing the surface of the mineral layer of the BC hydrogel membrane (the surface of the mineral layer is attached to a polytetrafluoroethylene sheet, and the edges of the BC hydrogel membrane are sealed with silicone grease), immerse it in the antimicrobial peptide solution and shake for 24 hours. This allows the catechol / quinone groups on the surface of the dopamine salt to undergo a Michael addition reaction with the amino groups of the antimicrobial peptide molecules and form covalent bonds, anchoring the antimicrobial peptide to the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with PBS buffer to remove the sealing sheet. The antimicrobial peptide solution used is Cecropin B, which is dissolved in PBS buffer and has a concentration of 1.0 mg / mL.

[0061] S5. The BC hydrogel membrane is sequentially rinsed with deionized water, freeze-dried, sterilized, and encapsulated to obtain the bacterial cellulose-based biomaterial.

[0062] Comparative Example 1

[0063] A method for preparing bacterial cellulose-based biomaterials, comprising the following steps:

[0064] S1. Prepare HS medium (components: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, 1.5 g / L citric acid monohydrate). Inoculate frozen Komagataeibacter accharivorans into HS plates and incubate at 30°C for 36 h to activate it. Then, take a single colony of Komagataeibacter accharivorans from the HS plate and inoculate it into HS medium. Incubate at 30°C with stirring at 180 rpm for 18 h to obtain the seed solution. Add the seed solution to HS medium at an inoculation rate of 5% and incubate statically at 30°C for 72 h to obtain BC hydrogel. Then, immerse the BC hydrogel in a 2% NaOH solution for 60 min. After removing it, wash it with deionized water until neutral. Finally, air dry the BC hydrogel at room temperature to obtain the BC hydrogel membrane.

[0065] S2. The BC hydrogel membrane is laid flat on a polytetrafluoroethylene plate and immersed in a dopamine hydrochloride solution. It is shaken at room temperature in the dark for 12 hours to allow dopamine to self-polymerize under the action of dissolved oxygen and form a polydopamine layer on the surface of the BC hydrogel membrane. Finally, the BC hydrogel membrane is rinsed with deionized water. The dopamine hydrochloride solution is prepared using Tris-HCl buffer solution with a pH of 9 and a concentration of 2.2 mg / mL.

[0066] S3. Next, the edges of the BC hydrogel membrane are sealed with silicone grease and immersed in the antimicrobial peptide solution. The membrane is shaken for 24 hours to allow the catechol / quinone groups on the surface of the dopamine salt to undergo a Michael addition reaction with the amino groups of the antimicrobial peptide molecules and form covalent bonds, thus anchoring the antimicrobial peptide to the BC hydrogel membrane. Finally, the BC hydrogel membrane with the sealing sheet is removed by rinsing with PBS buffer. The antimicrobial peptide solution is Cecropin B, which is dissolved in PBS buffer and has a concentration of 1.0 mg / mL.

[0067] S4. The BC hydrogel membrane is sequentially rinsed with deionized water, freeze-dried, sterilized, and encapsulated to obtain the bacterial cellulose-based biomaterial.

[0068] Comparative Example 2

[0069] A method for preparing bacterial cellulose-based biomaterials, comprising the following steps:

[0070] S1. Prepare HS medium (components: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, 1.5 g / L citric acid monohydrate). Inoculate frozen Komagataeibacter accharivorans into HS plates and incubate at 30°C for 36 h to activate it. Then, take a single colony of Komagataeibacter accharivorans from the HS plate and inoculate it into HS medium. Incubate at 30°C with stirring at 180 rpm for 18 h to obtain the seed solution. Add the seed solution to HS medium at an inoculation rate of 5% and incubate statically at 30°C for 72 h to obtain BC hydrogel. Then, immerse the BC hydrogel in a 2% NaOH solution for 60 min. After removing it, wash it with deionized water until neutral. Finally, air dry the BC hydrogel at room temperature to obtain the BC hydrogel membrane.

[0071] S2. Place the BC hydrogel membrane flat on a polytetrafluoroethylene plate, and uniformly drop zinc sulfate solution onto the surface of the BC hydrogel membrane. After dropping, let it stand for 40 minutes to allow the Zn solution to settle. 2+ The solution penetrates into the surface fiber network of the BC hydrogel membrane, and then the residual zinc sulfate solution is removed. Next, sodium phosphate solution is added dropwise to the surface of the BC hydrogel membrane in the same manner, allowing PO4 to penetrate. 3-It penetrates into the surface fiber network of the BC hydrogel membrane and interacts with Zn. 2+ The reaction occurs within the fiber network, generating zinc phosphate crystals in situ and forming a dense, porous mineral layer. Finally, the BC hydrogel membrane is rinsed with deionized water. The concentrations of zinc sulfate and sodium phosphate are 0.12 M, and the addition rate is 0.15 mL / cm³. 2 .

[0072] S3. Next, flip the BC hydrogel membrane over, seal the edges of the BC hydrogel membrane with silicone grease, immerse it in the antimicrobial peptide solution, and shake it for 24 hours. Finally, rinse the BC hydrogel membrane with PBS buffer to remove the sealing film. The antimicrobial peptide solution is Cecropin B, which is dissolved in PBS buffer and has a concentration of 1.0 mg / mL.

[0073] S4. The BC hydrogel membrane is sequentially rinsed with deionized water, freeze-dried, sterilized, and encapsulated to obtain the bacterial cellulose-based biomaterial.

[0074] Comparative Example 3

[0075] A method for preparing bacterial cellulose-based biomaterials, comprising the following steps:

[0076] S1. Prepare HS medium (components: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, 1.5 g / L citric acid monohydrate, 1 g / L ficus seed gum powder). Inoculate frozen Komagataeibacter accharivorans into HS plates and incubate at 30℃ for 36 h to activate it. Then, take a single colony of Komagataeibacter accharivorans from the HS plate and inoculate it into HS medium. Incubate at 30℃ and 180 rpm for 18 h to obtain the seed solution. Add the seed solution to HS medium at an inoculation rate of 5% and incubate statically at 30℃ for 72 h to obtain BC hydrogel. Then, immerse the BC hydrogel in a 2% NaOH solution for 60 min. After taking it out, wash it with deionized water until neutral. Finally, air dry the BC hydrogel at room temperature to obtain the BC hydrogel membrane.

[0077] The preparation steps of the fig seed gum powder are as follows: after cleaning and removing impurities, fig seeds are soaked in 45°C warm water for 3 hours, then crushed in a tissue homogenizer for 4 minutes. The pulp is filtered to remove fig seed residue to obtain gum solution. Two volumes of anhydrous ethanol are added to the gum solution, and the mixture is allowed to stand and precipitate. The precipitate is collected and the steps of water dissolution and ethanol precipitation are repeated to finally obtain a pure filter cake. The pure filter cake is then crushed, dried, ground, and sieved to obtain fig seed gum powder.

[0078] S2. Place the BC hydrogel membrane flat on a polytetrafluoroethylene plate, and uniformly drop zinc sulfate solution onto the surface of the BC hydrogel membrane. After dropping, let it stand for 40 minutes to allow the Zn solution to settle. 2+ The solution penetrates into the surface fiber network of the BC hydrogel membrane, and then the residual zinc sulfate solution is removed. Next, sodium phosphate solution is added dropwise to the surface of the BC hydrogel membrane in the same manner, allowing PO4 to penetrate. 3- It penetrates into the surface fiber network of the BC hydrogel membrane and interacts with Zn. 2+ The reaction occurs within the fiber network, generating zinc phosphate crystals in situ and forming a dense, porous mineral layer. Finally, the BC hydrogel membrane is rinsed with deionized water. The concentrations of zinc sulfate and sodium phosphate are 0.12 M, and the addition rate is 0.15 mL / cm³. 2 .

[0079] S3. Next, flip the BC hydrogel membrane over and immerse it in a dopamine hydrochloride solution. Shake it at room temperature in the dark for 12 hours to allow dopamine to self-polymerize under the action of dissolved oxygen and form a polydopamine layer on the surface of the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with deionized water. The dopamine hydrochloride solution was prepared using Tris-HCl buffer solution with a pH of 9 and a concentration of 2.2 mg / mL.

[0080] S4. After sealing the surface of the mineral layer of the BC hydrogel membrane (the surface of the mineral layer is attached to a polytetrafluoroethylene sheet, and the edges of the BC hydrogel membrane are sealed with silicone grease), immerse it in the antimicrobial peptide solution and shake for 24 hours. This allows the catechol / quinone groups on the surface of the dopamine salt to undergo a Michael addition reaction with the amino groups of the antimicrobial peptide molecules and form covalent bonds, anchoring the antimicrobial peptide to the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with PBS buffer to remove the sealing sheet. The antimicrobial peptide solution used is Cecropin B, which is dissolved in PBS buffer and has a concentration of 1.0 mg / mL.

[0081] S5. The BC hydrogel membrane is sequentially rinsed with deionized water, freeze-dried, sterilized, and encapsulated to obtain the bacterial cellulose-based biomaterial.

[0082] III. Performance Testing

[0083] (1) Microscopic morphological characterization

[0084] The bacterial cellulose-based biomaterial samples prepared in Examples 1-3 and Comparative Examples 1-3 were used to observe the microstructure of the side of each sample exposed to the external environment using a Hitachi High Technology Corporation SU8000 scanning electron microscope (SEM) (voltage 3kV).

[0085] (2) Swelling properties

[0086] The bacterial cellulose-based biomaterial samples prepared in Examples 1-3 and Comparative Examples 1-3 were freeze-dried and then immersed in phosphate-buffered saline solution to examine their swelling behavior. First, after removing any excess surface solution with a non-woven filter cloth, the weight of the swollen samples was recorded at specific time points (0.5h, 1h, 2h, 4h, 8h, 12h, 24h). The swelling rate of the biomaterial samples was calculated using the following formula:

[0087]

[0088] In the formula, W0 is the initial weight of the freeze-dried bacterial cellulose-based biomaterial sample, and Wt is the weight of the expanded sample at different time intervals.

[0089] (3) Breathability

[0090] Take bacterial cellulose-based biomaterial samples (1.5 cm in diameter) prepared in Examples 1-3 and Comparative Examples 1-3 above, and install them on the edge of the mouth of a non-corrosive, airtight glass bottle. Fill the glass bottle with 50 mL of deionized water (with a 1 cm gap between the water surface and the sample to avoid direct contact). Seal the glass bottle opening with PTFE tape. Weigh the entire measuring device (glass bottle, sample, water, PTFE tape) first, and then place the entire measuring device in an environment of 37°C and 85% humidity for 24 hours. Weigh it again after 24 hours, and calculate the water vapor transmission rate according to the following formula:

[0091]

[0092] In the formula, W1 and W2 are the final and initial total weights of the measuring device, respectively, and S is the actual infiltrated bacterial cellulose-based biomaterial sample area.

[0093] (4) In vitro antibacterial properties

[0094] The bacterial cellulose-based biomaterial samples prepared in Examples 1-3 and Comparative Examples 1-3 were used as test strains. *Escherichia coli* (O157:H7) and *Staphylococcus aureus* (S. aureus) were used to determine the antibacterial rate using the plate count method. Specifically, the bacterial cellulose-based biomaterial samples were cut into 10 mm diameter discs using a punch, sterilized under UV light for 30 min, and then placed in 24-well plates. Bacteria in the logarithmic growth phase were taken, and the bacterial concentration was adjusted. 100 μL of 10⁻⁶ styrene solution was added to each well. 6CFU / mL bacterial suspension was added dropwise to the surface of each sample and incubated at 37°C for 2 hours. Subsequently, 2 mL of LB medium was added to each well, and the samples were incubated at 37°C and 180 rpm for 2 hours. The resulting bacterial suspension was then diluted to an appropriate concentration. 100 μL of the diluted bacterial suspension was evenly spread onto a solid LB agar plate and incubated overnight at 37°C. The colony count was observed and recorded, and the antibacterial rate was calculated using the following formula:

[0095]

[0096] In the formula: N0 is the initial colony count, and N1 is the final colony count.

[0097] (5) Wound healing test

[0098] Female Sprague-Dawley rats (330-350g) were used as subjects in the animal experiments. Before surgery, rats were anesthetized intraperitoneally with 3% sodium pentobarbital at a dose of 1.0 mL / kg. After shaving the back of the rats, a full-thickness skin wound model (1 cm in diameter) was constructed by excising the dorsal skin. The wound was then covered and fixed with bacterial cellulose-based biomaterial samples prepared in Examples 1-3 and Comparative Examples 1-3, respectively, and clean gauze was placed around the wound for further fixation. On postoperative day 14, tissue was obtained from the wound area, fixed in 4% paraformaldehyde solution, and analyzed pathological sections of the wound tissue by hematoxylin and eosin (HE) staining to assess wound healing.

[0099] IV. Results Analysis

[0100] (1) Microscopic morphological characterization

[0101] The microstructures of the bacterial cellulose-based biomaterials prepared in Examples 1-3 and Comparative Examples 1-3 are as follows: Figure 1 As shown in the figure, AF represents the morphology of Examples 1-3 and Comparative Examples 1-3, respectively. It can be seen that Examples 1-3 and Comparative Examples 2 and 3 exhibit a fibrous porous network structure, with a large number of crystalline structures, namely zinc phosphate crystals, interspersed and filled in the interstices of the fibers, making the network structure more compact, but still retaining a large number of pores, forming a physical mineral layer barrier. In contrast, Comparative Example 1, due to the absence of a mineral layer modification step, only exhibits a fibrous porous network structure with loose pores.

[0102] (2) Swelling properties

[0103] The swelling ratios of the bacterial cellulose-based biomaterials prepared in Examples 1-3 and Comparative Examples 1-3 are as follows: Figure 2As shown, all samples exhibit high water absorption and swelling properties. After 24 hours, the swelling rates of Examples 1 and 2 reached over 1700%, while that of Example 3 was over 2850%. Comparative Example 1, which omitted the mineral layer modification step in Example 2, showed a slight increase in swelling rate compared to Example 2, though not by much. This may be because the mineral crystal filling in Example 2 had a certain but minor impact on water absorption and swelling. Comparative Example 1, which omitted the dopamine hydrochloride solution soaking step in Example 2, showed no significant change in swelling rate compared to Example 2. Comparative Example 3, which did not perform hydrophobic modification on the Ficus pumila seed gum powder in Example 3, showed a significant decrease in swelling rate to around 2300% compared to Example 3. This may be because ordinary Ficus pumila seed gum powder tends to fill the pores of the fiber network, which affects the water absorption and swelling of the fibers themselves.

[0104] (3) Breathability

[0105] The water vapor transmission rates of the bacterial cellulose-based biomaterials prepared in Examples 1-3 and Comparative Examples 1-3 are statistically analyzed and shown in Table 1 below:

[0106] Table 1: Water vapor transmission rate results

[0107] <![CDATA[Water Vapor Transmission Rate (gm -2 / day -1 )]]> 2031.3 2135.9 2016.7 2513.2 2164.5 1524.5

[0108] Generally speaking, the water vapor transmission rate should not be too high or too low. Too high a rate can lead to excessive water loss, causing wound drying and delaying healing; too low a rate can cause exudate to accumulate in the wound, which is also detrimental to wound healing. As can be seen from Table 1 above, the water vapor transmission rates of Examples 1-3 of this invention are all within a suitable range. However, Comparative Example 1, having lost its mineral layer, exhibits a significantly higher water vapor transmission rate compared to Example 2, reaching 2513.2 gm. -2 day -1 The water vapor permeability of Comparative Example 2 was higher than the ideal range, and there was no significant difference between Comparative Example 2 and Example 2. However, the water vapor permeability of Comparative Example 3 was significantly lower than that of Example 3, and was below the ideal range.

[0109] (4) In vitro antibacterial properties

[0110] The antibacterial rates of the bacterial cellulose-based biomaterials prepared in Examples 1-3 and Comparative Examples 1-3 are statistically analyzed and shown in Table 2 below:

[0111] Table 2: Antibacterial Rate Results

[0112] Antibacterial rate of E. coli O157:H7 (%) 99.8 99.5 99.7 99.4 97.4 99.5 Antibacterial rate of S. aureus (%) 98.6 98.2 98.7 98.0 95.9 98.5

[0113] As can be seen from Table 2 above, Examples 1-3 and Comparative Examples 1-3 of the present invention all exhibit good in vitro antibacterial effects, with only Comparative Example 2 showing a slight decrease in antibacterial rate compared to Example 2. However, the in vitro antibacterial test environment differs from that of actual wound application; therefore, further analysis of its actual antibacterial effect or its effect on promoting wound healing is needed.

[0114] (5) Wound healing test

[0115] The tissue staining analysis results of the bacterial cellulose-based biomaterials prepared in Examples 1-3 and Comparative Examples 1-3 are as follows: Figure 3 As shown, all experimental groups exhibited varying degrees of inflammatory response. Examples 1-3 showed relatively fewer inflammatory cells, especially Example 3, which formed a new epidermal layer and some blood vessels and hair follicles, indicating that Example 3 demonstrated the best wound healing ability. Comparative Examples 1 and 2 showed slightly worse results compared to Example 2, with a still higher number of inflammatory cells, suggesting that the barrier function of the mineral layer and the anchoring and sustained-release effect of the polydopamine layer on antimicrobial peptides are crucial. Comparative Example 3 also showed significantly worse results compared to Example 3, possibly because the common fig seed gum powder affected the porous structure of the BC fibers.

[0116] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing bacterial cellulose-based biomaterials, characterized in that the steps include... include: S1. Take *Odontobacterium micranthum*, and obtain BC hydrogel membrane through fermentation, purification, and drying; S2. Place the BC hydrogel membrane flat on a polytetrafluoroethylene plate, and uniformly drop zinc sulfate solution onto the surface of the BC hydrogel membrane. After dropping, let it stand for 30-40 minutes to allow the Zn solution to settle. 2+ The solution penetrates into the surface fiber network of the BC hydrogel membrane, and then the residual zinc sulfate solution is removed. Next, sodium phosphate solution is added dropwise to the surface of the BC hydrogel membrane in the same manner, allowing PO4 to penetrate. 3- It penetrates into the surface fiber network of the BC hydrogel membrane and interacts with Zn. 2+ The reaction occurs in the fiber network, generating zinc phosphate crystals in situ and forming a dense, porous mineral layer. Finally, the BC hydrogel membrane is rinsed with deionized water. S3. Then turn the BC hydrogel membrane over and immerse it in a dopamine hydrochloride solution. Shake it at room temperature in the dark for 6-12 hours to allow dopamine to self-polymerize under the action of dissolved oxygen and form a polydopamine layer on the surface of the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with deionized water. S4. After sealing the surface of the mineral layer of the BC hydrogel membrane, immerse it in the antimicrobial peptide solution and shake it for 12-24 hours. This allows the catechol / quinone groups on the surface of the polydopamine layer to undergo Michael addition reaction with the amino groups of the antimicrobial peptide molecules and form covalent bonds, thus anchoring the antimicrobial peptide to the BC hydrogel membrane. Finally, rinse the BC hydrogel membrane with PBS buffer. S5. The BC hydrogel membrane is sequentially rinsed with deionized water, freeze-dried, sterilized, and encapsulated to obtain the bacterial cellulose-based biomaterial.

2. The method for preparing a bacterial cellulose-based biomaterial according to claim 1, characterized in that, The specific operation of step S1 is as follows: Frozen *Coprinus comatus* was inoculated onto an HS plate and incubated at 28-30℃ for 36-48 h to activate it. Then, a single colony of *Coprinus comatus* from the HS plate was inoculated onto HS medium and incubated at 28-30℃ with stirring at 120-180 rpm for 18-36 h to obtain a seed solution. The seed solution was then added to HS medium at an inoculation rate of 4-5% and statically cultured at 28-30℃ for 72-120 h to ferment and obtain BC hydrogel. The BC hydrogel was then immersed in a 1-2% NaOH solution for 60-80 min, removed, and washed with deionized water until neutral. Finally, the BC hydrogel was air-dried at room temperature to obtain the BC hydrogel membrane.

3. The method for preparing a bacterial cellulose-based biomaterial according to claim 2, characterized in that, The *Komagataeibacter* strain is selected from one of *Komagataeibacter xylinus*, *Komagataeibacter saccharivorans*, or *Komagataeibacter hansenii*.

4. The method for preparing a bacterial cellulose-based biomaterial according to claim 2, characterized in that, The HS culture medium consists of: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, and 1.5 g / L citric acid monohydrate.

5. The method for preparing a bacterial cellulose-based biomaterial according to claim 2, characterized in that, The HS culture medium consists of: 20 g / L glucose monohydrate, 6 g / L peptone, 5 g / L yeast extract, 2.5 g / L anhydrous disodium hydrogen phosphate, 1.5 g / L citric acid monohydrate, and 1 g / L hydrophobic ficus seed gum powder. The preparation steps of the hydrophobic fig seed gum powder are as follows: After washing and removing impurities from fig seeds, soak them in warm water at 40-50℃ for 2-4 hours, then grind them using a tissue homogenizer for 3-5 minutes. Filter the pulp after grinding to remove the fig seed residue, obtaining a gum solution. Add 1.5-2.5 times the volume of anhydrous ethanol to the gum solution, allow it to settle, collect the precipitate, and repeat the steps of water dissolution and ethanol precipitation to finally obtain a pure filter cake. This cake is then crushed, dried, ground, and sieved to obtain fig seed gum powder. The fig seed gum powder is then prepared at a ratio of 1g:30... -40 mL of the solution was dissolved in deionized water at 35±2℃, and the pH was adjusted to 8-9 with NaOH. Then, 2-4% of the weight of the fig seed gum powder was added dropwise while stirring, and the reaction was carried out for 3-4 hours. After the reaction was completed, the pH of the reaction solution was adjusted to neutral with HCl. Then, 2-3 times the volume of anhydrous ethanol was added to the reaction solution, and the mixture was allowed to stand to precipitate. The precipitate was collected and the steps of water dissolution and ethanol precipitation were repeated to finally obtain a pure filter cake. The filter cake was then crushed, dried, ground, and sieved to obtain hydrophobic fig seed gum powder.

6. The method for preparing a bacterial cellulose-based biomaterial according to claim 1, characterized in that, In step S2, the concentrations of zinc sulfate and sodium phosphate are 0.08-0.12 M, and the dropping volume is 0.12-0.15 mL / cm³. 2 .

7. The method for preparing a bacterial cellulose-based biomaterial according to claim 1, characterized in that, In step S3, the dopamine hydrochloride solution is prepared using Tris-HCl buffer solution with a pH of 8-9 and a concentration of 1.5-2.2 mg / mL.

8. The method for preparing a bacterial cellulose-based biomaterial according to claim 1, characterized in that, In step S4, the antimicrobial peptide solution is selected from antimicrobial peptide Cecropin B or human defensin HD-5, which are dissolved in PBS buffer and have a concentration of 0.5-1.0 mg / mL.

9. The method for preparing a bacterial cellulose-based biomaterial according to claim 1, characterized in that, In step S4, the specific operation of sealing the mineral layer surface of the BC hydrogel membrane is to attach the mineral layer surface of the BC hydrogel membrane to a polytetrafluoroethylene sheet and seal the edges of the BC hydrogel membrane with silicone grease.

10. A bacterial cellulose-based biomaterial, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Cellulose antibacterial film and preparation method thereof

    CN111714693A

  • Bacterial cellulose-polydopamine-MXene-coated AgNPs antibacterial hemostatic sponge as well as preparation method and application thereof

    CN115944772A